“ROCKET TO ROCKET”: SEBUAH KISAH TENTANG CITA-CITA DAN HARAPAN - Yholanda Kunthi Anggriva; Mahendradewa Suminto; Agnes Karina Pritha Atmani (Journal of Animation and Games Studies, 2019)
Rockets are spacecraft, missiles, or flying vehicles that get a boost through rocket reactions to fluid materials. In this film the rocket represents dreams and hopes. The process of launching a rocket is the process of reaching someone's dream. The process of launching missiles into space is not easy, but that doesn't mean it can't. This film, invites the audience to be sure of hope and dare to fight for it. The creation of this animated film is presented in the form of 2D animation without using any narration or dialogue. As a support for the atmosphere, music is created that can build an atmosphere. Not forget the 12 principles of animation applied in this animated film to strengthen and improve the artistic impression as a support of visualization. The twodimensional animation technique is intentionally used because the visual form of 2D animation has a light but easy to remember impression.